Linezolid for the treatment of hospital-acquired pneumonia in a Chinese tertiary hospital - Lesher BA; Liu Z; Chen Y; Gao X (Dove Medical Press, 2015)
Beth A Lesher,1 Zhengyin Liu,2 Yixi Chen,3 Xin Gao11Pharmerit International, Bethesda, MD, USA; 2Department of Infectious Disease, Peking Union Medical College Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, People’s Republic of China; 3Pfizer Investment Co, Ltd, Beijing, People’s Republic of ChinaWe read with interest the study published by Song et al describing their retrospective analysis of the clinical response and hospital costs associated with the empiric use of vancomycin or linezolid therapy in patients with hospital-acquired pneumonia (HAP) in the People’s Republic of China.1 Results from matched comparisons showed similar clinical response (30.0% vs 31.7%; P=0.847) and treatment failure rates (55.0% vs 45.0%; P=0.289) but a significantly lower in-hospital mortality rate (3.3 vs 18.3%; P=0.013) for vancomycin-treated patients compared to linezolid-treated patients. Treatment failure rates (odds ratio [OR], 1.139; P=0.308) and risk of in-hospital mortality were comparable (OR, 0.186; P=0.055) between vancomycin- and linezolid-treated patients following further adjustment for an imbalance in variables between the matched treatment groups. Reported total hospital costs were not significantly different between vancomycin- (RMB 113,160) and linezolid (RMB 133,825)-treated patients (P=0.076).View original paper by Song et al